A dry electrode with online regulation of the degree of fiberization and a rolling process thereof
Patent Information
- Application Number
- CN202611179610.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-13
AI Technical Summary
然而,现有干法电极技术的纤维化程度缺乏定量表征手段和工艺调控模型,在工程实践中,技术人员通过肉眼或低倍光学显微镜观察极片表面形貌来粗略判断纤维化效果,判断标准主观性强,缺乏标准化、可量化的纤维化程度评价指标,更缺乏纤维化程度与辊压工艺参数之间的定量映射关系
本发明建立了PTFE纤维化程度指数与干法辊压关键工艺参数之间的定量映射模型,将纤维化程度从经验性定性描述提升为可计算、可设计的工程量化参数,通过正交实验设计和贝叶斯岭回归拟合获得,基于该模型,工艺人员只需根据目标孔隙率要求,即可快速获得第二辊压温区的辊温、轧制比和辊速梯度的最优设定值,无需反复试探,大幅缩短将新配方的工艺开发周期,该模型适用于磷酸铁锂、镍钴锰三元材料、钴酸锂、硅基复合材料等多种活性材料体系,为干法电极的规模化生产提供理论支撑。
Smart Images

Figure CN122907573A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery electrode manufacturing technology, specifically to a dry electrode with online control of the degree of fibrosis and its rolling process. Background Technology
[0002] With the booming development of the new energy vehicle industry and the rapid expansion of the energy storage market, the market has put forward increasingly stringent requirements for the energy density, power performance, and manufacturing cost of lithium-ion batteries. As the core component of lithium-ion batteries, the manufacturing process of the electrode directly determines the final performance of the battery. The traditional wet electrode manufacturing process uses N-methylpyrrolidone (NMP) as a solvent to disperse active materials, conductive agents, and binders in the solvent to form a slurry, which is then coated, dried, rolled, and other processes to form the electrode. This process has inherent drawbacks: NMP solvent is toxic and expensive, and the recycling process requires a complex condensation and distillation system, resulting in large equipment investment and high energy consumption, which significantly increases the battery manufacturing cost; the drying process requires drying tunnels, which occupy a large amount of factory space, and the energy consumption of the drying process accounts for more than 60% of the total energy consumption of electrode manufacturing; the wet process is limited by the rheological properties of the slurry and the drying shrinkage stress, and there is an upper limit to the loading of active materials in the electrode, making it difficult to meet the high energy density requirements.
[0003] Dry electrode technology uses polytetrafluoroethylene (PTFE) powder instead of traditional solution-based binders (such as PVDF). Under solvent-free conditions, mechanical shear force induces PTFE fiberization, forming a three-dimensional network framework that binds active material particles and conductive agent particles into a self-supporting electrode film. This film is then hot-pressed with a current collector, achieving a completely solvent-free manufacturing process. PTFE fiberization is the core physical mechanism of dry electrode film formation. When PTFE particles are subjected to shear force in a temperature range above their glass transition temperature but below their melting point, the PTFE molecular chains extend and orient along the shear direction, forming fibers with diameters of 50nm-500nm. These fibers intertwine to form a three-dimensional network structure, and the degree of fiberization directly determines the mechanical properties and pore structure of the dry electrode. However, existing dry electrode technologies lack quantitative characterization methods and process control models for the degree of fiberization. In engineering practice, technicians roughly judge the fiberization effect by observing the surface morphology of the electrode with the naked eye or a low-magnification optical microscope. This judgment is highly subjective, lacking standardized and quantifiable evaluation indicators for the degree of fiberization, and even more so, lacking a quantitative mapping relationship between the degree of fiberization and the rolling process parameters. Traditional dry-process electrodes have a uniform porosity distribution along the thickness direction. This single structure cannot simultaneously meet the conflicting requirements of electrode internal resistance and ion conduction.
[0004] In summary, existing dry electrode technologies suffer from drawbacks such as uncontrollable fiberization levels, monotonous porosity structures, and a lack of online quality feedback during manufacturing. There is an urgent need for a dry electrode and its rolling process that can establish a quantitative mapping relationship between process parameters and PTFE fiberization levels, achieve gradient porosity structures through segmented temperature zone rolling, and implement closed-loop quality control based on online detection. This is to meet the pressing demands of high-energy-density and high-power-density lithium-ion batteries for electrode manufacturing. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a dry electrode with online control of the degree of fiberization and its rolling process. The dry electrode includes a current collector and a self-supporting electrode film composited on the current collector. The self-supporting electrode film includes an outer layer region near the current collector and a central layer region away from the current collector along the thickness direction. The outer layer region has a porosity of 20%-35% and a PTFE fiberization degree index DoF≥0.7, while the central layer region has a porosity of 38%-55% and a DoF≤0.4, forming a gradient structure in which active material particles and conductive agent particles are wrapped by a three-dimensional network of PTFE fibers. The rolling process achieves gradient structure formation through three temperature zones of rolling: a preheating and compaction zone, a fiberization and film formation zone, and a cold setting zone. At the exit of the third rolling zone, terahertz time-domain spectroscopy is used to detect the porosity in real time. The rolling temperature and speed gradient of the second zone are automatically adjusted through closed-loop feedback of a PID controller, realizing quantitative design and online control of the degree of fiberization.
[0006] To solve the above-mentioned technical problems, the present invention provides the following technical solution: On the one hand, a dry electrode with online control of the degree of fibrosis, the dry electrode comprising a current collector and a self-supporting electrode film composited in the current collector; The self-supporting electrode film includes at least two regions with different porosities along its thickness direction, the at least two regions including an outer layer region close to the current collector side and a central layer region away from the current collector side; The porosity of the outer layer region is 20%-35%, and the porosity of the central layer region is 38%-55%. The degree of polytetrafluoroethylene fibrillation in the outer region The polytetrafluoroethylene fiberization index of the central layer region ; The self-supporting electrode membrane is composed of active material particles and conductive agent particles wrapped in a three-dimensional network of polytetrafluoroethylene fibers, and the self-supporting electrode membrane does not contain organic solvents. The active material has a mass fraction of ≥80% in the self-supporting electrode film.
[0007] Furthermore, the outer layer region also includes solid electrolyte particles embedded in the pores of the three-dimensional network of polytetrafluoroethylene fibers, wherein the volume fraction of the solid electrolyte particles is 5%-15%, and the median particle size of the solid electrolyte particles is [not specified]. The range is 50nm-500nm; The solid electrolyte is selected from at least one of sulfide solid electrolytes, oxide solid electrolytes, or polymer solid electrolytes; The sulfide solid electrolyte includes Cl, the oxide solid electrolyte includes lithium lanthanum zirconium oxide, and the polymer solid electrolyte includes polyoxyethylene alkyl solid electrolyte.
[0008] Furthermore, the active material is selected from at least one of lithium iron phosphate, nickel-cobalt-manganese ternary materials, lithium cobalt oxide, or silicon-based composite materials; The conductive agent is selected from at least one of Super-P carbon black, acetylene black, or carbon nanotubes. The total thickness of the self-supporting electrode film is 80μm-200μm; The thickness of the outer layer is 10μm-40μm on one side, and the thickness of the central layer is 30μm-120μm. The current collector is an aluminum foil or a copper foil, and the thickness of the current collector is 8μm-20μm.
[0009] On the other hand, a dry electrode rolling process method with online control of fiberization degree includes the following steps: S100. Based on the ternary mapping model of the degree of polytetrafluoroethylene fiberization, process parameters are pre-calculated, and active materials, conductive carbon black and polytetrafluoroethylene powder are mixed according to the target ratio and dispersed in a dry atmosphere by an air jet mill to obtain a uniform mixed powder with an average particle size D50 < 20 μm. The dew point of the dry atmosphere is < -40℃. S200. The uniformly mixed powder is evenly spread by a feeding roller and enters the first roller pressing temperature zone, i.e., the preheating and compaction section. The roller temperature of the first roller pressing temperature zone is 60℃-90℃. The rolling ratio of the first roller pressing temperature zone is... The ratio is 1.2-1.5, so that the uniformly mixed powder is formed into a pre-compressed sheet; S300. The pre-compressed sheet is placed into the second rolling temperature zone, i.e., the fiberization film-forming section. The rolling temperature of the second rolling temperature zone is 100℃-140℃. The rolling ratio of the second rolling temperature zone is... The speed gradient is 1.5-2.5, introducing a double-roller speed gradient. The coupling effect of the temperature gradient formed by the roller temperature conduction and the shear force gradient generated by the roller speed gradient makes the degree of polytetrafluoroethylene fiberization in the outer layer near the roller surface higher than that in the central layer. Under the action of shear force, polytetrafluoroethylene is stretched and fiberized to form a three-dimensional network of PTFE fibers, thus obtaining a fiberized membrane material. In the same continuous rolling process, a gradient structure with low porosity in the outer layer and high porosity in the central layer is formed. S400. The fibrous membrane material is placed into the third rolling temperature zone, i.e., the cold setting section. The rolling temperature of the third rolling temperature zone is 60℃-80℃. The rolling ratio of the third rolling temperature zone is... For a value of 1.1-1.3, the three-dimensional network of PTFE fibers is fixed and the internal stress is reduced to obtain a self-supporting electrode film; S500: At the outlet of the third roller pressing temperature zone, the porosity of the self-supporting electrode film obtained in S400 is detected in real time using terahertz time-domain spectroscopy to obtain a porosity detection value. The porosity detection value is compared with the target porosity value to obtain a deviation value. The deviation value is input into a PID controller, and the PID controller adjusts the roller temperature of the second roller pressing temperature zone and / or the roller speed gradient of the dual rollers. S600: The self-supporting electrode film, after online testing by S500, is hot-pressed and bonded to the current collector at the composite roller press station, and then wound up by the tension control roller to obtain the dry electrode product.
[0010] Furthermore, in S100, the target ratio is 80%-95% by mass of active material, 1%-5% by mass of conductive carbon black, and 1%-8% by mass of polytetrafluoroethylene powder; The median particle size D50 of the polytetrafluoroethylene powder is 3μm-10μm.
[0011] Furthermore, in S100, the ternary mapping model is the polytetrafluoroethylene fiberization degree index. The mapping model between the process parameters is used to solve the optimal settings of the roll temperature in the second roll pressing zone, the rolling ratio in the second roll pressing zone, and the roll speed gradient of the twin rolls based on the target porosity. The ternary mapping model is as follows: Where DoF is the degree of fibrosis index and , The rolling temperature of the second rolling temperature zone. This refers to the rolling ratio in the second roll pressing temperature zone. This represents the double-roll speed gradient in the second rolling temperature zone. , =2.0、 As the baseline process parameters, , , and The target porosity refers to the model parameters obtained by fitting orthogonal experimental data. It has a linear relationship with DoF: ,in, This refers to the natural packing porosity of polytetrafluoroethylene powder before it is fiberized. This is the material correlation coefficient.
[0012] Furthermore, the aforementioned The quantitative characterization method is as follows: Take a cross-sectional or surface sample of the fibrous membrane material obtained from S300 and photograph it under a scanning electron microscope at a magnification of [missing information]. The image is binarized to extract the fiber skeleton. The number of fiber crossover points per unit area is counted. The maximum crossover point density obtained from the count of fiber crossover points is used as a benchmark for normalization to obtain... value; The orthogonal experimental data were obtained through at least three-factor, three-level orthogonal experiments, where the three factors are the rolling temperature of the second rolling temperature zone. The rolling ratio of the second roll pressing temperature zone and the twin-roll speed gradient in the second roll pressing temperature zone The mapping model was fitted using Bayesian ridge regression to linearize the equation. We performed a fitting test and used five-fold cross-validation to ensure the coefficient of determination. .
[0013] Furthermore, in S300, the mechanism by which the degree of fiberization in the contact layer region is higher than that in the central layer region is as follows: heat from the roller surface of the second roller pressing temperature zone is conducted to the interior of the pre-pressed sheet to form a temperature gradient. The temperature of the contact layer of the pre-pressed sheet is higher than that of the central layer. At the same time, the shear force generated by the double roller speed gradient decreases from the surface layer to the central layer along the thickness direction of the pre-pressed sheet. Under the effect of thermo-mechanical coupling, the degree of fiberization of polytetrafluoroethylene in the contact layer region is higher than that in the central layer region. This forms a dense region with low porosity, and the polytetrafluoroethylene fiberization index of the central layer region... This forms a high-porosity loose zone, thereby obtaining a gradient porosity distribution along the thickness direction; In S200, the double-roll speed gradient in the first rolling temperature zone is ≤0.05m / min; In S400, the double-roll speed gradient in the third roller pressing temperature zone is ≤0.05m / min; In S300, the dual-roller speed gradient is achieved by servo motors that independently drive the upper and lower rollers. It is the absolute value of the difference between the linear speed of the upper roller and the linear speed of the lower roller; In S300, the rolling linear speed in the second rolling temperature zone is 1m / min-10m / min; In the S600 process, the temperature of the hot-press bonding is 100℃-130℃, and the pressure is 0.5MPa-2MPa. The current collector is an aluminum foil or a copper foil, with the aluminum foil used as the positive electrode current collector and the copper foil used as the negative electrode current collector.
[0014] Furthermore, in the S500, the calibration method for the terahertz time-domain spectrum is as follows: The true porosity of standard samples with different porosities was determined using mercury intrusion porosimetry, and the terahertz transmission delay time of the standard samples was measured simultaneously. Establish calibration curves ,in, Porosity This is the terahertz transmission delay time. and These are calibration coefficients; The frequency range of the terahertz time-domain spectrum is 0.2THz-3THz, and the scanning frequency is... Porosity detection accuracy is ; The trigger condition for the control loop is: when the deviation value exceeds... At that time, the PID controller starts parameter fine-tuning, and the adjustment range of the parameter fine-tuning is the roller temperature of the second roller pressing temperature zone. And / or the dual-roller speed gradient m / min; When the deviation value of three consecutive tests exceeds When this happens, an alarm is triggered and the machine is shut down.
[0015] Compared with existing technologies, this dry electrode with online control of fiberization degree and its rolling process have the following advantages: This invention establishes a quantitative mapping model between the PTFE fiberization degree index and key process parameters of dry rolling, elevating the fiberization degree from an empirical qualitative description to a calculable and designable engineering quantitative parameter. This model is obtained through orthogonal experimental design and Bayesian ridge regression fitting. Based on this model, process engineers can quickly obtain the optimal settings for the roll temperature, rolling ratio, and roll speed gradient in the second rolling temperature zone simply by considering the target porosity requirements, eliminating the need for repeated trials and significantly shortening the process development cycle for new formulations. This model is applicable to various active material systems such as lithium iron phosphate, nickel-cobalt-manganese ternary materials, lithium cobalt oxide, and silicon-based composite materials, providing theoretical support for the large-scale production of dry electrodes.
[0016] This invention utilizes a three-stage segmented temperature zone rolling process. It leverages the temperature gradient formed by heat conduction from the roller surface to the interior of the pre-pressed sheet in the second rolling zone, and the thermo-mechanical coupling effect of the shear force generated by the roller speed gradient decreasing from the surface to the center layer along the sheet thickness direction. This achieves active differential control of the PTFE fiberization degree along the electrode thickness direction. This process results in a low-porosity dense region (DoF ≥ 0.7) in the contact layer and a high-porosity loose region (DoF ≤ 0.4) in the center layer, producing a dry electrode with a gradient porosity distribution along the thickness direction. The outer low-porosity dense structure adheres tightly to the current collector, resulting in low contact resistance and high interfacial bonding strength, effectively reducing the electrode's internal resistance. The high-porosity loose structure in the center layer provides wetting space and a rapid lithium-ion diffusion channel for the electrolyte, significantly reducing concentration polarization.
[0017] Other advantages, objectives and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination or study, or may be learned from the practice of the invention. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort.
[0019] Figure 1 This is a flowchart of a dry electrode rolling process for online control of the degree of fiberization. Detailed Implementation
[0020] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with the accompanying drawings and preferred embodiments, is provided below.
[0021] All embodiments of the present invention were carried out in a dry cleanroom with a temperature of 22±2°C, a relative humidity of less than 1%, a dew point of less than -40°C, and a cleanliness level of 10. The following embodiments and comparative examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention.
[0022] To address the technical problems of long process development cycles and poor batch stability caused by the lack of quantitative characterization methods and process control models for the degree of polytetrafluoroethylene (PTFE) fiberization in existing dry electrode technologies, and to resolve the performance contradiction between electrode internal resistance and ion conduction due to the difficulty in fabricating gradient porosity structures in existing roll forming processes, this invention provides a dry electrode roll forming process method with online control of fiberization degree. This method achieves differentiated control of the degree of PTFE fiberization through three-stage segmented temperature zone roll forming, thereby preparing a dry electrode with a gradient porosity distribution along the thickness direction. Furthermore, by combining terahertz time-domain spectroscopy online detection and PID closed-loop feedback control, real-time monitoring of porosity and automatic adjustment of process parameters are achieved. Figure 1 As shown, the specific steps of a dry electrode rolling process for online control of fiberization degree in an embodiment of the present invention are as follows: S100. Based on the ternary mapping model of the degree of polytetrafluoroethylene fiberization, process parameters are pre-calculated, and active materials, conductive carbon black and polytetrafluoroethylene powder are mixed according to the target ratio and dispersed in a dry atmosphere by an air jet mill to obtain a uniform mixed powder with an average particle size D50 < 20 μm. The dew point of the dry atmosphere is < -40℃. S200. The uniformly mixed powder is evenly spread by a feeding roller and enters the first rolling temperature zone. The rolling temperature of the first rolling temperature zone is 60℃-90℃. The rolling ratio of the first rolling temperature zone is... The ratio is 1.2-1.5, so that the uniformly mixed powder is formed into a pre-compressed sheet; S300. The pre-compressed sheet is placed into the second rolling temperature zone, the rolling temperature of the second rolling temperature zone is 100℃-140℃, and the rolling ratio of the second rolling temperature zone is... The speed gradient is 1.5-2.5, introducing a double-roller speed gradient. The polytetrafluoroethylene is stretched and fiberized under shear force to form a three-dimensional network of PTFE fibers, thus obtaining a fibrous membrane material. S400. The fibrous membrane material is placed in the third rolling temperature zone, the rolling temperature of the third rolling temperature zone is 60℃-80℃, and the rolling ratio of the third rolling temperature zone is... For a value of 1.1-1.3, the three-dimensional network of PTFE fibers is fixed and the internal stress is reduced to obtain a self-supporting electrode film; S500: At the outlet of the third roller pressing temperature zone, the porosity of the self-supporting electrode film obtained in S400 is detected in real time using terahertz time-domain spectroscopy to obtain a porosity detection value. The porosity detection value is compared with the target porosity value to obtain a deviation value. The deviation value is input into a PID controller, and the PID controller adjusts the roller temperature of the second roller pressing temperature zone and / or the roller speed gradient of the dual rollers. S600: The self-supporting electrode film, after online testing by S500, is hot-pressed and bonded to the current collector at the composite roller press station, and then wound up by the tension control roller to obtain the dry electrode product.
[0023] Example 1 This embodiment uses a three-factor, three-level orthogonal experiment to change the rolling temperature of the second rolling zone. The rolling ratio in the second roll pressing temperature zone The two-roll speed gradient in the second roll pressing temperature zone The fiber cross-point density of self-supporting electrode membrane cross-section samples under various experimental conditions was measured. A quantitative mapping model between the polytetrafluoroethylene fiberization degree index (DoF) and process parameters was established by Bayesian ridge regression fitting. This model enables the function of reversing the optimal setting value of process parameters based on the target porosity, providing a model-driven parameter design basis for the subsequent preparation of gradient porosity electrodes.
[0024] This embodiment adopts Orthogonal experimental setup to examine three key process parameters: the rolling temperature in the second rolling zone. The rolling ratio in the second roll pressing temperature zone The double-roll speed gradient in the second roll pressing temperature zone .
[0025] Each of the three parameters has three levels: roll forming temperature. The three levels are 90℃, 110℃, and 130℃; rolling ratio The three levels are 1.4, 1.8, and 2.2; twin-roll speed gradient. The three levels were 0.1 m / min, 0.3 m / min, and 0.5 m / min, for a total of 27 experimental conditions.
[0026] In this embodiment, the active material is lithium iron phosphate (LFP), and the median particle size of the lithium iron phosphate is... The median particle size of the polytetrafluoroethylene powder is 8 μm, and the conductive agent used is Super-P carbon black. The thickness is 6μm, and the mass ratio of the three components is lithium iron phosphate: Super-P carbon black: polytetrafluoroethylene powder = 90:4:6.
[0027] In this embodiment, the roll temperature in the first roll pressing zone is fixed at 75°C, and the rolling ratio in the first roll pressing zone is... The rolling speed gradient of the two rolls in the first rolling temperature zone is fixed at 1.3, the rolling temperature in the third rolling temperature zone is fixed at 70℃, and the rolling ratio in the third rolling temperature zone is fixed at 1.3. The temperature gradient of the two rollers in the third roller pressing zone is fixed at 1.15, the roller speed gradient is fixed at 0 m / min, the roller pressing linear speed of all groups is fixed at 5 m / min, and the preparation conditions for each group are a width of 100 mm and a target thickness of [missing information]. μm self-supporting electrode film samples. After each set of experiments, a cross-sectional sample was cut from the obtained self-supporting electrode film.
[0028] Five regions of the cross-sectional sample were randomly selected under a field emission scanning electron microscope. A secondary electron image with a magnification of 5000x was taken for each region. The images were then subjected to grayscale conversion, Otsu algorithm threshold segmentation and binarization processing to extract the fiber skeleton. The number of fiber cross-points per unit area was counted, and the average value of the five regions was taken as the average cross-point density of the sample group.
[0029] In all 27 groups of experiments in this embodiment, , , The maximum crossover density was obtained under the condition of m / min, and the maximum crossover density was 0.85. Using the maximum crosspoint density as the baseline value of 1.00, the average crosspoint density of all 27 groups of samples is divided by 0.85. The resulting ratio is the fiberization degree index (DoF) value of each group of samples. DoF is a dimensionless index with a value range of 0-1.
[0030] Model fitting was performed on 27 sets of experimental data, and the mapping model was analyzed. Perform the transformation, let The linearized equation is obtained as follows: The linearized equation was fitted using Bayesian ridge regression. The fitted model parameters were K=1.31, the temperature exponential coefficient β=2.0, and the rolling ratio exponential coefficient... The exponential coefficient of the roll speed gradient Five-fold cross-validation was used to evaluate the fitting results, and the coefficient of determination of the cross-validation was... The mean value is 0.92, indicating that the mapping model has high prediction accuracy. Four additional validation experiments were conducted, with parameter combinations not included in the aforementioned 27 orthogonal experiments. The measured DoF values were compared with the predicted DoF values of the mapping model. The maximum relative error was less than [value missing]. When the rolling temperature T=125°C and the rolling ratio Double roller speed gradient When the velocity is 0.25 m / min, the DoF value is calculated by substituting it into the model. ;when At that time, the calculated DoF ≈ 0.31. This embodiment successfully established the relationship between the polytetrafluoroethylene (PTFE) fiberization degree index DoF and the rolling temperature T in the second rolling zone, as well as the rolling ratio, through a three-factor, three-level orthogonal experiment and Bayesian ridge regression fitting. Double roller speed gradient Quantitative mapping model between them: The linear relationship between porosity P and DoF was also determined. The mean R² of the five-fold cross-validation was 0.92, and the maximum relative error of the validation experiment was less than 7%, which can provide a quantitative calculation basis for the inverse solution of the optimal setting value of process parameters under different target porosities.
[0031] In this embodiment, the target porosity The linear relationship between DoF and porosity was defined as follows: the true porosity of each group of samples was determined by mercury porosimetry, and the DoF value of each sample was plotted on the x-axis, with porosity as the y-axis. Perform linear regression on the ordinate to obtain a linear relationship. For the lithium iron phosphate / Super-P / polytetrafluoroethylene material system of this embodiment, the calibration results are as follows: , .
[0032] This embodiment successfully established the relationship between the polytetrafluoroethylene (PTFE) fiberization degree index (DoF) and the rolling temperature of the second rolling zone through a three-factor, three-level orthogonal experiment and Bayesian ridge regression fitting. Rolling ratio Double roller speed gradient Quantitative mapping model between The porosity was also calibrated. Linear relationship with DoF Five-fold cross-validation The mean value is 0.93, and the maximum relative error of the verification experiment is less than [missing value]. This demonstrates that the mapping model has high prediction accuracy and engineering applicability, and can provide a quantitative calculation basis for the inverse solution of the optimal setting value of process parameters under different target porosities.
[0033] Example 2 This embodiment utilizes the DoF mapping model established in Example 1 to obtain the optimal process parameter settings for the second rolling temperature zone based on the inverse solution of the target gradient porosity distribution. A dry electrode with a gradient porosity structure is prepared using a three-stage gradient rolling process. The formation of the porosity gradient distribution is verified point by point along the thickness direction using a focused ion beam scanning electron microscope. Finally, a coin cell is assembled to verify the effect of the gradient structure on improving electrochemical performance.
[0034] The total thickness of the target electrode in this embodiment is: μm, the desired porosity distribution is: 30% porosity in the outer layer (0-25μm and 125-140μm), and 25% porosity in the central layer (25-125μm). According to the linear relationship calibrated in Example 1 The inverse kinematics calculation yields the required DoF value for the outer region. The required DoF value for the central layer region is .
[0035] The mapping model obtained according to Example 1 To ensure that the DoF of the contact layer area reaches above 0.71, the rolling temperature of the second rolling zone is selected. The rolling ratio in the second roll pressing temperature zone The two-roll speed gradient in the second rolling temperature zone m / min, substituting the above parameters into the mapping model, calculate to obtain To satisfy the outer region Requirements.
[0036] For the central layer region, under the same parameter conditions, due to the temperature gradient formed by the heat conduction from the roller surface into the interior of the pre-compressed sheet, the central layer temperature is... Meanwhile, the shear force generated by the double-roller speed gradient decreases from the surface layer to the center layer along the sheet thickness direction. The shear force in the center layer is estimated to be 40% of that in the surface layer. , , m / min (shear force according to) Calculation, equivalent Substituting m / min into the mapping model, we can calculate... Satisfy the central layer area Requirements.
[0037] In this embodiment, a three-stage gradient rolling process is implemented using a three-stage independent temperature-controlled rolling mill unit. The three-stage independent temperature-controlled rolling mill unit has a roller diameter of 150mm, a roller width of 300mm, and the roller surface is treated with hard chrome plating. The process parameters for each stage are as follows: First roll pressing temperature zone (preheating and compaction section): Roll temperature is 75℃, rolling ratio The roller speed gradient of the twin rollers is 0 m / min, and the linear speed is 5 m / min.
[0038] Second roller pressing temperature zone (fiberization film formation section): Roller temperature is Rolling ratio Twin-roller speed gradient 0.25 m / min (the linear speed of the upper roller is greater than that of the lower roller, and the difference in linear speed between the upper and lower rollers is 0.25 m / min), and the linear speed is 5 m / min.
[0039] Third roll forming zone (cold setting section): Roll temperature is Rolling ratio The roller speed gradient of the twin rollers is 0 m / min, and the linear speed is 5 m / min.
[0040] The raw material ratio is the same as in Example 1, namely lithium iron phosphate: Super-P carbon black: polytetrafluoroethylene powder = 90:4:6.
[0041] After the above three-stage rolling process, a self-supporting electrode film is obtained with a thickness of 140 μm. The obtained self-supporting electrode film is prepared by focusing an ion beam perpendicular section. Under field emission scanning electron microscopy, a measurement point is taken every 10 μm along the thickness direction from one side surface to the other side surface, for a total of 15 measurement points. The porosity at each measurement point is statistically analyzed. The measurement results are as follows: the porosity is 29%-31% in the depth range of 0-10 μm, 30%-33% in the depth range of 10-20 μm, and 32%-35% in the depth range of 20-30 μm. Corresponding to the outer layer region near the first roller surface, the average porosity of this region is approximately 32%, with porosity ranging from 42% to 46% in the 30-60 μm depth range, 44% to 48% in the 60-90 μm depth range, and 43% to 46% in the 90-120 μm depth range. These figures correspond to the central layer region, where the average porosity is approximately 45%, with porosity ranging from 30% to 32% in the 120-130 μm depth range and 28% to 30% in the 130-140 μm depth range. Corresponding to the other outer layer region near the second roller surface, the maximum porosity difference along the thickness direction is 15%, verifying the formation of a gradient porosity structure.
[0042] A gradient structure self-supporting electrode film was placed on a 15 μm thick aluminum foil. C. Hot-pressing composite under 1 MPa conditions yields the dry-process electrode product. The dry-process electrode product is cut into 15 mm diameter discs, and coin cells are assembled using lithium metal as the counter electrode. A mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) with a volume ratio of 1:1 is used as the electrolyte to prepare a control dry-process electrode with uniform porosity. The control dry-process electrode is prepared using a single-temperature zone rolling process (single-temperature zone). Rolling ratio 1.8 The speed is 5 m / min and the linear velocity is 5 m / min. All other conditions are exactly the same as those for the gradient electrode. The same specification coin cell is assembled.
[0043] Discharge capacity tests were conducted at 2C rate. The discharge capacity of the gradient structure dry electrode was 152 mAh / g, while the discharge capacity of the uniform porosity control dry electrode was 141 mAh / g, representing an approximately 7.8% increase in 2C rate discharge capacity. After 200 cycles at 1C rate, the capacity retention of the gradient structure dry electrode was 94.5%, while that of the uniform porosity control dry electrode was 89.2%. The cycling stability of the gradient structure electrode was significantly better than that of the control electrode. These results indicate that the gradient porosity structure effectively reduces the internal resistance of the electrode and ensures rapid lithium-ion conduction, resulting in significant improvements in both rate performance and cycling stability.
[0044] Based on the DoF mapping model established in Example 1, this embodiment successfully obtained the optimal process parameters for the second rolling temperature zone through inverse kinematics. , , m / min, using a three-stage gradient rolling process to prepare an outer layer with a porosity of approximately The porosity of the central layer is approximately Gradient difference approximately The gradient structure dry electrode was verified by point-by-point porosity measurement along the thickness direction using focused ion beam scanning electron microscopy, confirming the successful formation of the gradient distribution. Electrochemical tests showed that the 2C rate discharge capacity of the gradient structure dry electrode was 7.8% higher than that of the uniform porosity control electrode, demonstrating that the gradient porosity structure can simultaneously meet the comprehensive performance requirements of low internal resistance and high ion conductivity.
[0045] Example 3 This embodiment establishes the terahertz time-domain spectral transmission delay time. With porosity calibration curves between This study achieves online detection of the porosity of a self-supporting electrode film. Under normal production conditions, a temperature step disturbance is artificially applied to the second roller pressing temperature zone. The porosity response difference between the closed-loop control mode and the open-loop no-feedback mode is compared to verify that the PID closed-loop control system can quickly suppress disturbances and restore the porosity deviation to the target value. Dynamic adjustment capability within [a certain range].
[0046] In this embodiment, six sets of lithium iron phosphate dry electrode standard samples with different porosities were prepared. The porosities of the six standard samples were 22%, 30%, 38%, 45%, 50%, and 55%, respectively. The porosity values were determined by mercury intrusion porosimetry. The terahertz transmission spectra of each standard sample were measured using a terahertz time-domain spectrometer with a frequency range of 0.2 THz-3 THz and a frequency resolution of 1 GHz. The delay time of the terahertz transmission pulse of each standard sample relative to the time when no sample was placed was extracted. to delay time Porosity measured by mercury intrusion porosimetry (x-axis) Perform linear regression on the ordinate to obtain the calibration curve: The coefficient of determination of the calibration curve The calibration error is less than The time for a single terahertz time-domain spectral scan is less than 50 ms.
[0047] In this embodiment, the parameters of the PID controller are obtained by tuning using the Ziegler-Nichols method, and the proportional coefficient is... Integral coefficient Differential coefficients The adjustment cycle is 0.5s.
[0048] Under normal production conditions, the target porosity is set as follows: The production parameters are exactly the same as those of the three-stage gradient rolling process in Example 2.
[0049] Under stable production conditions, a +10℃ step disturbance is artificially applied to the temperature of the second roll pressing zone, that is, the temperature of the second roll pressing zone is increased from 125℃ to 135℃, while keeping all other process parameters unchanged, and the porosity response curve over time is observed in open-loop mode (no feedback regulation) and closed-loop mode (PID feedback regulation enabled).
[0050] In open-loop mode, a temperature step disturbance intensifies the fiberization of PTFE, causing the porosity to decrease from 40% to approximately 34%, with a porosity shift of up to [value missing]. The porosity decreased by 6%, exceeding the acceptable range of ±1.5% of the target value. The porosity decrease did not recover within 5 minutes of continuous observation, resulting in a large number of unqualified products during continuous production.
[0051] In closed-loop mode, the terahertz time-domain spectroscopy probe detects the porosity deviation in real time. This deviation is input to the PID controller, which outputs an adjustment signal within 1.2 seconds, controlling the roll temperature in the second rolling zone to decrease from 135°C. The entire closed-loop adjustment process lasts approximately 6-8 seconds, ultimately stabilizing the porosity between 39.5% and 40.5%, with a maximum deviation of less than ±1.5%. Further adjustments to the roll temperature in the second rolling zone are then made under normal production conditions. A 10℃ step disturbance occurs when the roll temperature in the second roll pressing zone drops from 125℃ to 115℃. In closed-loop mode, the porosity increases from 40% to approximately 44%, and the PID controller corrects the porosity to between 39.8% and 40.3% within approximately 7 seconds, with the deviation controlled within ±1.2%.
[0052] This embodiment establishes the terahertz time-domain spectral delay time. With porosity calibration curves between , With a single scan time of less than 50ms, millisecond-level online detection of porosity is achieved. Under conditions of artificially applied ±10℃ roller temperature step disturbance, closed-loop control remains at 6. Within 8 seconds, the porosity deviation will be restored to within ±1.5% of the target value, while in open-loop mode, the porosity will continue to deviate to ±4-6% of the target value. The method combining online terahertz time-domain spectroscopy detection with PID closed-loop control can effectively suppress the impact of process disturbances on porosity, significantly improving product consistency and manufacturing yield.
[0053] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A dry electrode rolling process method with online control of fiberization degree, characterized in that, The steps of this method are as follows: S100. Based on the ternary mapping model of the degree of polytetrafluoroethylene fiberization, process parameters are pre-calculated, and active materials, conductive carbon black and polytetrafluoroethylene powder are mixed according to the target ratio and dispersed in a dry atmosphere by an air jet mill to obtain a uniform mixed powder with an average particle size D50 < 20 μm. The dew point of the dry atmosphere is < -40℃. S200. The uniformly mixed powder is evenly spread by a feeding roller and enters the first roller pressing temperature zone, i.e., the preheating and compaction section. The roller temperature of the first roller pressing temperature zone is 60℃-90℃. The rolling ratio of the first roller pressing temperature zone is... The ratio is 1.2-1.5, so that the uniformly mixed powder is formed into a pre-compressed sheet; S300. The pre-compressed sheet is placed into the second rolling temperature zone, i.e., the fiberization film-forming section. The rolling temperature of the second rolling temperature zone is 100℃-140℃. The rolling ratio of the second rolling temperature zone is... The speed gradient is 1.5-2.5, introducing a double-roller speed gradient. The coupling effect of the temperature gradient formed by the roller temperature conduction and the shear force gradient generated by the roller speed gradient makes the degree of polytetrafluoroethylene fiberization in the outer layer near the roller surface higher than that in the central layer. Under the action of shear force, polytetrafluoroethylene is stretched and fiberized to form a three-dimensional network of PTFE fibers, thus obtaining a fiberized membrane material. In the same continuous rolling process, a gradient structure with low porosity in the outer layer and high porosity in the central layer is formed. S400. The fibrous membrane material is placed into the third rolling temperature zone, i.e., the cold setting section. The rolling temperature of the third rolling temperature zone is 60℃-80℃. The rolling ratio of the third rolling temperature zone is... The stress is 1.1-1.
3. The PTFE fiber three-dimensional network is fixed and the internal stress is reduced to obtain a self-supporting electrode film. S500: At the outlet of the third roller pressing temperature zone, the porosity of the self-supporting electrode film obtained in S400 is detected in real time using terahertz time-domain spectroscopy to obtain a porosity detection value. The porosity detection value is compared with the target porosity value to obtain a deviation value. The deviation value is input into a PID controller, and the PID controller adjusts the roller temperature of the second roller pressing temperature zone and / or the roller speed gradient of the dual rollers. S600: The self-supporting electrode film, after online testing by S500, is hot-pressed and bonded to the current collector at the composite roller press station, and then wound up by the tension control roller to obtain the dry electrode product.
2. The dry electrode rolling process method for online control of fiberization degree according to claim 1, characterized in that, In S100, the target ratio is 80%-95% by mass of active material, 1%-5% by mass of conductive carbon black, and 1%-8% by mass of polytetrafluoroethylene powder. The median particle size D50 of the polytetrafluoroethylene powder is 3μm-10μm.
3. The dry electrode rolling process method for online control of fiberization degree according to claim 1, characterized in that, In S100, the ternary mapping model is the polytetrafluoroethylene fiberization degree index. The mapping model between the process parameters is used to solve the optimal settings of the roll temperature in the second roll pressing zone, the rolling ratio in the second roll pressing zone, and the roll speed gradient of the twin rolls based on the target porosity. The ternary mapping model is as follows: Where DoF is the degree of fibrosis index and , The rolling temperature of the second rolling temperature zone. This refers to the rolling ratio in the second roll pressing temperature zone. This represents the two-roll speed gradient in the second rolling temperature zone. , =2.0、 As the baseline process parameters, , , and These are the model parameters obtained through fitting orthogonal experimental data; the target porosity P and DoF satisfy a linear relationship: Where Po is the natural packing porosity of polytetrafluoroethylene powder before fiberization, k is the material correlation coefficient, and the target porosity is... It has a linear relationship with DoF: ,in, This refers to the natural packing porosity of polytetrafluoroethylene powder before it is fiberized. This is the material correlation coefficient.
4. The dry electrode rolling process method for online control of fiberization degree according to claim 3, characterized in that, The The quantitative characterization method is as follows: Take a cross-sectional or surface sample of the fibrous membrane material obtained from S300, perform binarization processing on the image under a scanning electron microscope to extract the fiber skeleton, count the number of fiber cross-points per unit area, and normalize the obtained maximum cross-point density based on the number of fiber cross-points to obtain... value.
5. The dry electrode rolling process method for online control of fiberization degree according to claim 1, characterized in that, In S200, the double-roll speed gradient in the first rolling temperature zone is ≤0.05m / min; In S400, the double-roll speed gradient in the third roller pressing temperature zone is ≤0.05m / min; In S300, the dual-roller speed gradient It is the absolute value of the difference between the linear speed of the upper roller and the linear speed of the lower roller; In S300, the rolling linear speed in the second rolling temperature zone is 1m / min-10m / min; In the S600 process, the temperature of the hot-press bonding is 100℃-130℃, and the pressure is 0.5MPa-2MPa. The current collector is an aluminum foil or a copper foil, with the aluminum foil used as the positive electrode current collector and the copper foil used as the negative electrode current collector.
6. The dry electrode rolling process method for online control of fiberization degree according to claim 1, characterized in that, In the S500, the calibration method for the terahertz time-domain spectrum is as follows: The true porosity of standard samples with different porosities was determined using mercury intrusion porosimetry, and the terahertz transmission delay time of the standard samples was measured simultaneously. Establish calibration curves ,in, Porosity This is the terahertz transmission delay time. and These are calibration coefficients; The frequency range of the terahertz time-domain spectrum is 0.2THz-3THz, and the scanning frequency is... ; When the deviation value exceeds At that time, the PID controller starts parameter fine-tuning, and the adjustment range of the parameter fine-tuning is the roller temperature of the second roller pressing temperature zone. And / or the dual-roller speed gradient m / min; If the deviation value of three consecutive tests exceeds ±3%, an alarm will be triggered and the machine will be shut down.
7. A dry electrode with online control of fiberization degree, applicable to the rolling process of a dry electrode with online control of fiberization degree as described in any one of claims 1-6, characterized in that, The dry electrode includes a current collector and a self-supporting electrode film composited in the current collector; The self-supporting electrode film includes an outer layer region and a central layer region; The porosity of the outer layer region is 20%-35%, and the porosity of the central layer region is 38%-55%. The degree of polytetrafluoroethylene fibrillation in the outer region The polytetrafluoroethylene fiberization index of the central layer region ; The self-supporting electrode membrane is composed of active material particles and conductive agent particles wrapped in a three-dimensional network of polytetrafluoroethylene fibers, and the self-supporting electrode membrane does not contain organic solvents. The active material has a mass fraction of ≥80% in the self-supporting electrode film.
8. A dry electrode with online control of fiberization degree according to claim 1, characterized in that, The outer layer region also includes solid electrolyte particles embedded in the pores of the three-dimensional network of polytetrafluoroethylene fibers. The volume fraction of the solid electrolyte particles is 5%-15%, and the median particle size of the solid electrolyte particles is [not specified]. The range is 50nm-500nm.
9. A dry electrode with online control of fiberization degree according to claim 1, characterized in that, The active material is selected from at least one of lithium iron phosphate, nickel-cobalt-manganese ternary materials, lithium cobalt oxide, or silicon-based composite materials; The conductive agent is selected from at least one of Super-P carbon black, acetylene black, or carbon nanotubes.